NICHE MARKET: RESPONSE OF STUDENTS OF BUDDHIST DHARMA UNIVERSITY ON KAWASAKI BRAND MOTORCYCLES : CERUK PASAR : TANGGAPAN MAHASISWA UNIVERSITAS BUDDHI DHARMA PADA MOTOR MEREK KAWASAKI - Sonny Santosa (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2021)
Currently, the growth of motor vehicle market share is increasing in the global market including In Indonesia, one of the motorcycle brands that attract market share in the community is Kawasaki motorcycles, especially Kawasaki motorcycle type W175, this type of motorcycle is classified as a retro motorcycle that has quite a lot of enthusiasts of this type of motorcycle, this study was conducted to see the market share opportunities for a "Kawasaki motorcycle" in the community since the Father of the Unitary State of the Republic of Indonesia uses motorcycles under the banner of the Kawasaki brand to do "blusukan" in the community Tangerang City. Analysis approach conducted through conjoin. There are three types of attributes tested in this study, namely Kawasaki street motorcycle type or type attributes with three levels of Ninja, Z, Street models, then value programs attributes with Kawasaki Road Service (KRS), Kawasaki Racing Academy (KRA), and Kawasaki Journey (KJ) levels. Moreover, lastly, design attributes with Sporty level, Classic. And Modern. The data of this study was obtained using questionnaires distributed to 147 respondent students who all met the criteria set at the beginning of this study, sampling method using proportionate sampling and based on the results of the analysis obtained the conclusion that respondents have more attractiveness of this Kawasaki brand motorcycle because the street attribute with a value of essential values of 41,248 with conjoining analysis model formed is ri = 0.099x11 – 0.256x12 + 0.157x13 + 0.031x21 + 0.063x22 + 0.094x23 – 0.161x31 – 0.321x32 – 0.482x33 + 14.259, while Pearson's R correlation test of 0.171 with a significant level above 0.05 this indicates that respondents do not see any correlation of interest which means that students are doubtful to take an interest in this Kawasaki brand motorcycle